Extracurricular educational programs and school readiness: Evidence from a quasi-experiment with preschool children - Anna Makles; Kerstin Schneider (University of Wuppertal, Schumpeter School of Business and Economics, 2014)
This paper adds to the literature on extracurricular early childhood education and child development by exploiting unique data on an educational project in Germany, the Junior University (JU). Utilizing a quasi-experimental study design, we estimate the causal short-term effect of JU enrollment on cognitive outcomes and show that attending extra science courses with preschool classes leads to significantly higher school readiness. Although the size of the effect is relatively small, the results are plausible and pass various robustness checks. Moreover, in comparison with other programs this intervention is cost-effective.
urn:nbn:de:hbz:468-20140905-103654-8
Keywords: I20; I21; I28; J13; 330; early childhood education; early interventions; school readiness